KOMPETENSI GURU DALAM MELAKSANAKAN PEMBELAJARAN DI TK MUSLIMAT NU 31 SUMBERSARI KOTA MALANG - Suhartini Suhartini; Anwar Sa’dullah; Yorita Febry Lismanda (UNISMA, 2020)
Teacher competence is a set of knowledge, skills and behaviors that must be mastered by every educator. teacher competency is also a principal agent in the implementation of the process of learning and learning activities that occur at every level of the school. Based on data exposure The purpose of this study was to determine the preparation of learning plans in TK Muslimat NU 31, knowing the implementation of the teaching and learning process at TK Muslimat NU 31, and knowing the implementation of teaching and learning assessments at TK Muslimat NU 31. The preparation of the learning plan at this institution is entirely designed by the homeroom teacher starting from the program, RPPM, and RPPH which is updated every new school year. for Prota is designed by all educators, it's just that prota at this institution has not been updated for a long time. The implementation of learning activities at this institution starts from the material, media, learning methods, and assessment techniques used in accordance with the planned learning plan. Implementation of the assessment of the results of learning activities at this institution using 3 techniques including rating techniques for the achievement of child development scales (rating scale) with a checklist format, anecdotal note assessment techniques, and techniques for evaluating the notes of the work. The assessment instrument uses 9 intelligence guidelines.